Las relaciones escritas de san Josemaría sobre sus visitas a Francisco Morán (1934-1938) / Written account by St. Josemaría Escrivá about his visits to Francisco Morán (1934-1938) - Santiago Casas Rabasa (Studia et Documenta)
Written account by St. Josemaría Escrivá about his visits to Francisco Morán (1934-1938): Between 1934 and 1938, Josemaría Escriva met with Francisco Morán, vicar general of the dioceses of Madrid, to speak about various issues relating to his person and his apostolates. The founder of Opus Dei left written records of these meetings and in the following article they are transcribed. All are preceded by a short introduction, giving the content its proper context.